Development of an Assessment Instrument in Class X Geomatics of SMK Negeri 2 Samarinda for the 2022/2023 Academic Year on Height Difference Measurement Materials Using the Flat Angle Tool Based on the 2013 Curriculum - Pitauli, Udur (PT Literasi Nusantara Publisher, 2022)
Assessment is the process of collecting information or evidence through measurements, interpret, describe and interpret the evidence of measurement results. This research aims to describe the feasibility assessment instrument developed to measure the ability of affective, cognitive and psychomotor learners Geomatics Skills Competency Class X SMK 2 Samarinda the subject matter of height difference measurements using a waterpass. This research is the development of research in the form of an assessment instrument based on the curriculum of 2013. The method used is the Research and Development (R & D). Steps being used is the stage and the potential problems, the data collection phase, the stage of product design, design validation stage, stage design revisions, and test phase of the product. Items will be generated in this study is the assessment instruments in the subject matter of height difference measurements using a waterpass. Feasibility instruments are measured based on the validity, reliability and practicality of the instrument. Based on the results of the study, the percentage of the validity of the assessment instruments affective look for 97.22%, 91.67% increase in construction validation, validation language by 86.67%. Cognitive assessment instrument validation looks for 87.50%, validating the content of 81.67%, 87.50% increase in construction validation, validation language by 86.67%, and validation practicality of 87.50%. Psychomotor assessment instruments amounted to 87.50% face validation, validation of the content of 85.42%, 89.58% increase in construction validation, validation language by 81,67%, and validation practicality of 81,25%.